INTEGRATED FARMING MODEL OF SMALL RUMINANTS IN DELI SERDANG, NORTH SUMATRA - INDONESIA - Kusumastuti, T. A.; Sarim, S.; Masyhuri, M. (Diponegoro University, 2015)
This research was done to measure the added value of goat and sheep with cut and carry systemand influencing factors of goat/sheep productivity and to measure the added value of manure to palmproductivity. The research was done in Deli Serdang Regency by determining two districts as researcharea: Tanjung Morawa District and Bangun Purba District. Location was determined by purposivesampling technique based on population of small ruminants and area of oil palm plantation in bothdistricts. Sample consisted of 50 goat farmers and 50 sheep farmers. Results indicated that farmers have18 to 24 heads of goats or sheep. Performance of goat and sheep reproduction tended to similar togenereral performance. Amount of doe, feed from palm oil and intercropped plant, livestock type andlocation influence significantly at livestock productivity (P<0.01). Goat contributed manure 16.86% and11.26% of total palm trees in Tanjung Morawa and Bangun Purba, respectively, while sheep contributedmanure 21.49% and 22.56% of total palm trees, respectively. Therefore, it was necessary to increasepopulation of livestock, to increase technology and diversification of production. It may be done by establishing partnership with local government, animal of science office and private corporation .